Prophetic Leadership: A Human Decision-Making Model in Islamic Educational Institutions - Purnomo, Halim (Journal of Islamic Communication and Counseling, 2025)
This article aims to explain the role of prophetic leaders in humanist decision making in Islamic educational institutions. This research method is a literature study in which data is compiled to corroborate previous articles about decision making by leaders in Islamic educational institutions. This article focuses more on implementing prophetic qualities as a model of consideration in decision making in Islamic educational institutions. This article concludes that decision making through consideration of prophetic traits can present empowering, wise, humanist decisions, creating a work culture, strengthening teamwork, regeneration and Islamic character education, because decisions are always taken through various considerations of subjects, objects, work environment, staff characters and problem solvers.